An econometric analysis of the mental-health effects of major events in the life of older individuals - Maarten Lindeboom; France Portrait; Gerard van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2002)
Major events in the life of an older individual, such as retirement, a significant decrease in income, death of the spouse, disability, and a move to a nursing home, may affect the mental health status of the individual. For example, the individual may enter a prolonged depression. We investigate this using unique longitudinal panel data that track labor market behavior, health status, and major life events, over time. To deal with endogenous aspects of these events we apply fixed effects estimation methods. We find some strinkingly large effects of certain events on the occurence of depression. We relate the results to the health care and labor market policy towards older individuals.
Keywords: I18; 330; Death; retirement; income loss; disease; depression; health indicators; widowhood; care; panel data; endogeneity; fixed effects